1981
DOI: 10.1126/science.213.4507.544
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazine Formation During Investigations of Amino Acid Racemization in Dipeptides

Abstract: The formation of diketopiperazines from the dipeptides isoleucylglycine and glycylisoleucine was investigated at 132 degrees C over the pH range approximately 2 to 10. At pH 6.2, approximately 50 percent of the original dipeptides were converted to the diketopiperazines during the heating experiments. Hydrolysis of the diketopiperazines can yield either the original dipetide or an inverted dipeptide product. The isoleucine in the diketopiperazines was the most highly epimerized component in the system. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 7 publications
0
71
0
Order By: Relevance
“…6 The Power of Enzymes as Catalysts Wolfenden and Snider the half-time for hydrolysis of a single peptide bond. 14,15 That may explain the fact that proteins in higher organisms, which must survive for days or weeks, are usually N-acetylated, whereas N-acetylation is seldom observed in proteins from microorganisms with short generation times. 14 Next, we considered the hydrolysis of the internucleotide linkages in nucleic acids.…”
Section: Degrees Of Difficulty Of Biological Reactions In Watermentioning
confidence: 99%
“…6 The Power of Enzymes as Catalysts Wolfenden and Snider the half-time for hydrolysis of a single peptide bond. 14,15 That may explain the fact that proteins in higher organisms, which must survive for days or weeks, are usually N-acetylated, whereas N-acetylation is seldom observed in proteins from microorganisms with short generation times. 14 Next, we considered the hydrolysis of the internucleotide linkages in nucleic acids.…”
Section: Degrees Of Difficulty Of Biological Reactions In Watermentioning
confidence: 99%
“…showed that linear peptides containing isoleucine residue cyclizedto 2,5-diketopiperazines 21 . Cyclic dipeptides have been suggested as easily formed peptides in the chemical evolutionary process 22 and important compounds in the development of homochirality 23 , because of theireasy formation from amino acids and the difference between diastereomers in hydrophobicity.The topic of this research is the simple chiral cyclic dipeptides (cyclo-(alanyl-alanine): Homo-L-CP (1) and Hetero-CP (2)) shown in Figure 1.In particular, the epimerization and ring-opening reactions are investigated in basic aqueous solutions.The epimerization of Homo-L-CP (1) and (3) will proceed at first from the hydrogen abstraction step to give solvated anion intermediates (4) and (5) 15 .…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…Amino acid residues in diketopiperazines have been found to undergo rapid racemization at both neutral and basic pH values (7)(8)(9)(10)(11). Racemization in aspartame solutions heated at neutral pH should thus take place primarily in the diketopiperazine decomposition product.…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in the diketopiperazine pathway since results obtained in this laboratory (7) and in earlier work (8)(9)(10) had demonstrated that amino acid residues in diketopiperazines are highly susceptible to racemization at both neutral and basic pH values. Since the presence of D amino acids in the human diet may have a variety of consequences, many of which are only poorly understood (11)(12)(13), it would be important to establish the rate of racemization of aspartic acid and phenylalanine in aspartame and its diketopiperazine decomposition product.…”
mentioning
confidence: 99%
See 1 more Smart Citation